Romantic Love and Violence against Women from a Gender Approach (Global Journal of Human-Social Science, 2022)
Romantic love is dangerous for many women Violence against them VAW and femicides increase and are mostly perpetrated by their ex partners The Objective of the present study was to describe the personal interpretations of Romantic Love and VAW of men and women who go to the University in La Paz the study has a qualitative approach of the explanatory descriptive type based on focus groups and a scale Despite sharing some indicators men and women interpret them differently but these respond to the traditional image of romantic love where VAW is normalized so a possible way to counteract it is by deconstructing romantic love and the gender stereotypes that they promote it
Keywords: romantic love; holistic love; young people attending university; gender roles and stereotypes and violence against women (VAW)